Apathetic Thyroid Storm with Cardiorespiratory Failure, Pulmonary Embolism, and Coagulopathy in a Young Male with Graves’ Disease and Myopathy - Abuobeida Ali; Wail Mostafa; Cornelius Fernandez; Habib Ahmad; Nyi Htwe (Case Reports in Endocrinology)
A 38-year-old gentleman presented with thyroid storm with multiorgan involvement in the form of heart failure (thyrotoxic cardiomyopathy), respiratory failure (respiratory muscle fatigue), hepatic dysfunction, fast atrial fibrillation, pulmonary embolism, and disseminated intravascular coagulation (DIC). His Graves’ disease (GD) remained undiagnosed for nearly 8 months because apart from weight loss, he has not had any other symptoms of thyrotoxicosis. The presentation of thyroid storm was atypical (apathetic thyroid storm) with features of depression and extreme lethargy without any fever, anxiety, agitation, or seizure. There were no identifiable triggers for the thyroid storm. Apart from mechanical ventilation and continuous veno-venous renal replacement therapy in the intensive care unit, he received propylthiouracil (PTU), esmolol, and corticosteroids, which were later switched to carbimazole and propranolol with steroids being tapered down. He was diagnosed with thyrotoxic myopathy which, like GD, remained undiagnosed for long (fatigability). A high index of suspicion and a multidisciplinary care are essential for good outcome in these patients.